Eater-oriented knowledge framework for reducing salt and dietary sodium intake (scoping review) - Endaltseva, Alexandra; Coeurquetin, Paul; Thomas-Danguin, Thierry; Poulain, Jean-Pierre; Tibère, Laurence; Dupuy, Anne (Frontiers in Nutrition, 2023)
Salt and dietary sodium are ubiquitously present in daily food practices and, at the same time, reducing salt intake presents an important public health issue. Given such an ambivalent position of salt in human diet, we argue that public health guidelines towards dietary sodium reduction require an eater-oriented knowledge framework. In this article we are making the first steps towards a flexible interdisciplinary database which would include nutritional, socio-economic, cultural, material, and socio-psychological determinants of salt consumption for comprehensive public health campaigns. We employ an explorative scoping review of academic articles and reports, limiting our review to the original data on salt or sodium consumption published in English or French between 2000 and 2022. We describe salt consumption as research object, identifying its representation in different research fields, data sources, methodologies, samples, and links with nutritional recommendations. We synthesize existing approaches via four eater-oriented categories: Socio-demographic and cultural descriptors of salt consumers; Knowledge, attitudes, and beliefs on nutritional norms; Salt practices associated with dietary or medical regimes; Salt materialities: interactions and contexts. In each category, we identify the dominant relational features, i.e., what kind of ‘eater-salt’ relation is being put forward. We thus build an interdisciplinary documentary base of dietary sodium consumption factors. We discuss the results, suggesting that comprehensive nutritional policies for global salt reduction require interdisciplinary eater-oriented data frameworks.